Entomocidal Effect of Some Essential Oils: An alternative for Synthetic Pesticides in the Control of Dermestes maculatus Degeer 1774 (Coleoptera: Dermestidae) - Abbati Nasiru; Mohammed Suleiman (UMYU Journal of Microbiology Research)
Realizing the detrimental effect of synthetic pesticides on the environment, non-target organisms and human health.  The scientific community's interest in searching for and providing safe, natural and effective pesticides  Using the residual contact approach, the essential oils of Thymus vulgaris L. and Syzygium aromaticum L. (TEO and EOSA) were assessed against Dermestes maculatus in a laboratory setting.  Steam distillation was used to extract the oils.  Four concentrations (2.5, 5, 7.5, and 10%) were prepared using acetone as a solvent and applied individually to 15 g of smoke-dried C. gariepinus.  For five days, newly emerged adults, third-instar larvae, and newly laid pest eggs were exposed to the treated fish samples.  The results showed that both oils had varying larvicidal and adulticidal activities against D. maculatus.  Similarly, the EOs significantly decreased the pest's ability to lay eggs and hatch.  EOSA was the most effective treatment in all cases; it had the lowest LC50 and LT50 and the most effects at all dosages.  Consequently, EOSA and TEO could manage D. maculatus infesting smoke-dried C. gariepinus.